Content Based Image Retrieval System Using Integrated Feature Extraction Approach - Subhashree Sukla, Jyostnarani Tripathy, Anjali Behera, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This article implemented an efficient content-based image retrieval (CBIR) system using integrated feature extraction approach where spatial dependence matrix (SDM) is utilized to extract the texture features from the given images while translation invariant discrete wavelet transform(TIDWT) employed for low-level feature extraction. Further, this approach considered Tanimoto distance for showing the effectiveness of proposed hybrid CBIR system. Extensive experimental analysis discloses that proposed hybrid CBIR system improves efficiency tremendously over conventional CBIR systems.